2013
DOI: 10.1002/maco.201307126
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical behavior of new experimental TiNbZrAl alloys for dental applications

Abstract: The corrosion behavior of two new TiNbZrAl alloys together with the cp-Ti was investigated for dental applications. All samples were tested by electrochemical impedance spectroscopy (EIS) performed in artificial saliva with different pH (5.6 and 4.5), fluoride (2000 ppm F À ) and caffeine (1 mg/mL) contents. Additionally, scanning electron microscopy (SEM) was performed to observe the surface morphology after 1 day immersion in the test solution. The presence of 1 mg/mL caffeine in acidified fluoridated artifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Moreover, in order to obtain quantitative information about the EIS data, the equivalent circuit model was employed. Considering all the Nyquist plots are characterized by a semicircle and the phase angle shows only one “peak” over the whole frequency range in the Bode plots for all samples, which is a typical nature of the single film on the surface of the alloys, an equivalent circuit model (R s (Q p R P )), widely used for the fit of a single film on the surface of titanium alloys is adopted , as illustrated in Fig. .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in order to obtain quantitative information about the EIS data, the equivalent circuit model was employed. Considering all the Nyquist plots are characterized by a semicircle and the phase angle shows only one “peak” over the whole frequency range in the Bode plots for all samples, which is a typical nature of the single film on the surface of the alloys, an equivalent circuit model (R s (Q p R P )), widely used for the fit of a single film on the surface of titanium alloys is adopted , as illustrated in Fig. .…”
Section: Resultsmentioning
confidence: 99%
“…The impedance spectra were displayed as Nyquist and Bode (impedance modulus and phase angle vs . frequency) diagrams .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, good cell adhesion is greatly attributed to the presence of a 2-nm thick layer of amorphous Nb 2 O 5 on them. In addition, they also found that the Ti-19.1Nb-8.8Zr (wt.%) SMA exhibit higher corrosion resistance than NiTi SMAs [ 193 ], and even compared with pure Ti [ 232 ]. Bai et al further compared in vivo bone tissue biocompatibility of Ti-Nb alloys with pure Ti, the results indicated that Ti-Nb alloys had a comparable osteocompatibility to pure Ti while using micro-CT and histological evaluations, as shown in Figure 33 [ 231 ].…”
Section: Porous Ni-free Shape Memory Alloysmentioning
confidence: 99%
“…By controlling pore forming agent, the larger pore size of 800–1000 μm and high open porosity can be obtained by vacuum sintering from alloy powders, as shown in Figure 35 d. Xu et al fabricated porous Ti-25 wt.% Nb alloys with porosity even reaching 70% by sintering using polyurethane as space-holder, as shown in Figure 36 [ 243 ]. In addition, the pores shape of porous Ni-free SMAs is mainly determined by the particle shape of the pore-forming agent and it can be easily adjusted [ 232 ].…”
Section: Porous Ni-free Shape Memory Alloysmentioning
confidence: 99%